2017
DOI: 10.1016/j.ifset.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

High pressure pre-treatment of Moringa oleifera seed kernels prior to aqueous enzymatic oil extraction

Abstract: High pressure processing (HPP) was applied as a pre-treatment on Moringa oleifera (MO) kernels, for the first time, prior to aqueous enzymatic extraction (AEE) of the MO oil, and the effect of this pre-treatment is reported in terms of the free oil recovery and the nature of the cream emulsions formed. The HPP pre-treatments (50-250 MPa, 20-60 ⁰C, 10-60 min) generally resulted in higher free oil recoveries and thinner emulsion layers from ground-sieved kernels than the whole kernels. Optimization of the HPP pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Several parameters can be optimized to maximize recovery, including the seeds' size, moisture content, applied pressure, and temperature [89]. Aqueous enzymatic extraction has also been approached with positive outcomes, with up to 70% oil recovery [90,91], with easier phase separation efficiency when kernels are previously submitted to high pressure treatments, an increasingly common technique in the food industry [92]. One report on cold extraction of M. stenopetala seeds, variety Marigat, gave 35.7% of oil [64], which corresponds to an efficiency superior to 79%.…”
Section: Oil Extraction and Applicationsmentioning
confidence: 99%
“…Several parameters can be optimized to maximize recovery, including the seeds' size, moisture content, applied pressure, and temperature [89]. Aqueous enzymatic extraction has also been approached with positive outcomes, with up to 70% oil recovery [90,91], with easier phase separation efficiency when kernels are previously submitted to high pressure treatments, an increasingly common technique in the food industry [92]. One report on cold extraction of M. stenopetala seeds, variety Marigat, gave 35.7% of oil [64], which corresponds to an efficiency superior to 79%.…”
Section: Oil Extraction and Applicationsmentioning
confidence: 99%
“…Enzymatic aqueous extraction employs enzymes that hydrolyze and break cell walls of the material, making the structure more permeable and further exposing the oil component [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…All oil extraction methods conducted in this study were based on studies done by Mat Yusoff et al . (2016, 2017), and were performed on the ground‐sieved MO kernels.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of MO kernels, Mat Yusoff et al . (2017) reported that the HPP pre‐treatment successfully modified the MO protein structure into a form with less emulsifying ability; thus a smaller amount of oil was emulsified, which resulted in a thinner cream emulsion layer and 4.19% (w/w) higher free oil recovery as compared to the use of AEE alone . The study also reported a 4.98% (w/w) increase in free oil recovery when the AEE was pre‐treated by boiling (100 °C, 5 min) – this boiling pre‐treatment was conducted in earlier studies prior to an AEE of MO oil to inactivate the natural hydrolytic enzymes in the seed kernels …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation